The role of anti-aging approaches in managing hypogonadism in sedentary older males - Abdel-Sater, Khaled A. (Frontiers in Aging, 2024)
IntroductionWith thirty percent of the world’s population not getting enough exercise, Worldwide, physical inactivity ranks as one of the most common causes of premature mortality. Rapid drops in physical activity, decreased mobility, and early morbidity are aging characteristics. As the population over 80 continues to rise, aging raises the danger of age-related illnesses and changes in hormone release.AimUnderstanding the aging process is useful in developing pharmacological therapies and identifying therapeutic targets for age-related testosterone deficiency. Therefore, this study’s purpose is to present a thorough evaluation of the effects of anti-aging strategies on testosterone levels in older, inactive men.MethodsA literature search was completed for clinical and preclinical studies published in English between 2014 and 2024 related to age, sedentary life, testosterone, and anti-aging strategies.ResultsA sedentary lifestyle and low testosterone are linked to a vicious cycle. A sedentary lifestyle lowers testosterone levels, which leads to depression, exhaustion, low energy, and weakened bone and muscle strength. These effects exacerbate the detrimental consequences of aging and physical inactivity. Anti-aging techniques can prevent and treat age-related diseases, including calorie restriction, a balanced diet, regular exercise, weight control, diabetes management, and quitting smoking. Regular exercise raises total testosterone, free testosterone, and muscle steroidogenesis. In older men, testosterone replacement treatment increases bone density, cholesterol, protein synthesis, strength, erectile function, sexual desire, and general cognitive performance. However, some studies suggest dehydroepiandrosterone supplementation may provide health improvements without negative effects, potentially reversing arterial aging and reducing cardiovascular disease risk.ConclusionThis article evaluates the prospects for anti-aging procedures to assist in reducing the adverse effects of aging and physical inactivity in men.